Gender, manumission, and the Roman freedwoman - Perry, Matthew J. 1973- (Cambridge University Press, 2014)
Gender, Manumission, and the Roman Freedwoman examines the distinct problem posed by the manumission of female slaves in ancient Rome. The sexual identities of a female slave and a female citizen were fundamentally incompatible, as the former was principally defined by her sexual availability and the latter by her sexual integrity. Accordingly, those evaluating the manumission process needed to reconcile a woman's experiences as a slave with the expectations and moral rigor required of the female citizen. The figure of the freedwoman - fictionalized and real - provides an extraordinary lens into the matter of how Romans understood, debated, and experienced the sheer magnitude of the transition from slave to citizen, the various social factors that impinged upon this process, and the community stakes in the institution of manumission
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; Women slaves / Rome / History; Slaves / Emancipation / Rome / History; Freilassung; Sklavin; Rom; Rome / Social conditions; Rome / History; Römisches Reich